Akar Pemikiran Hukum Islam Liberal: Analisis Terhadap Pemikiran Hukum Islam Ibrahim Hosen: The Roots of Liberal Islamic Law Thought: A Study of Ibrahim Hosen Islamic Law Thought - Hamdani, Zaid; Abdul Rahim, Rahimin Affandi (Online Journal of Research in Islamic Studies, 2020)
Liberal Islamic law, in terms of terminology, is in fact an extension of the Liberal Islamic ideology pioneered by young intellectuals from Western universities. The Liberal Islamic Movement is a continuation of the Islamic modernist movement that emerged in the early 19th century in the Islamic world as a response to the interaction of the Islamic world with Western civilization. Such Islamic modernism was influenced by Western ways of thinking based on rationalism, humanism, secularism and liberalism. Liberal Islam is a new stream of thinking among Muslims. From this it can be concluded that the way of thinking of Liberal Muslims is to make a new conclusion to something out of the ordinary. One of the key figures whom some observers considered as the main pioneer of Liberal Islamic law was Ibrahim Hosen. He was known as an Islamic law scholar who always presents thoughtful ideas related to Islamic law beyond the thinking of other scholars of his contemporaries. The following short essay will try to reveal the thoughts of Ibrahim Hosen in the field of Liberal Islamic law. And we will attempt to see whether or not his thoughts are in line with the teachings and beliefs of the Liberals of Islamic law.